Imam Yusuf Zadeh and his methodology in his book Najah Al-Qari Sharh Sahih Al-Bukhari - abdulkerim, Abudula Abulimliti (Journal of Islamic Sciences, 2021)
Imam Abu Muhammad Abdullah bin Muhammad bin Yusuf bin Abdul Manan Al-Hilmi Al-Amassi is one of the most prominent scholars of the twelfth century in the Ottoman Empire, especially in the islamic science of readings and hadith As for his book (Najah Al-Qari, Sahih Al-Bukhari), it is a great, useful and comprehensive book, the author has emptied his can and exerted his effort until he showed it to the people, a comprehensive collector to views of predecessors, Riwayeten and dirayeten, including to successor sayings with all honesty and care. And that caption all sides jurisprudence of hadith. Might he was hope with that to be his that book a comprehensive reference for everyone who wants to delve into the hadith and its sciences. And this research aims to definition the author’s political, social life and scientific state in addition to studying the hadith in his time. As such that research encompass definition the book “Najah Al-Qari” to Sahih Al-Bukhari, and encompass rank of Al-Bukhari to the Ottoman sultans, and the definition the author’s curriculum in that. It adopted the inductive approach to extrapolate the texts and collect them within the limits of the research topic. It also adopted the descriptive approach in analyzing and interpreting texts and drawing conclusions, adhering to the limits of the research in focusing on the approach of Imam Yusuf Effendi Zadeh in his book Najah Al Qari. Among the most prominent results that I reached is that Imam Yusuf Effendizadeh's approach in his book Analytical Method, as it is considered in his method of explanation as an explanation mixed with the text.
Keywords: Yusuf Effendi Zadeh; The Ottoman Caliphate; Najah Al-Qari; Sahih Al-Bukhari; Explanation of the Prophetic Hadith